Analisis Faktor Intensitas Penerangan Lokal Terhadap Kelelahan Mata Di Industri Pembuatan Sepatu “X” Kota Semarang - Sari Eka Wahyuni; Bina Kurniawan; - Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
One of the problems that interfere with the work of labor is a problem concerning the lighting / poor lighting or excessive lighting.The intensity of illumination that there are influenced by factors of a quantity lighting and the quality of illumination (glare). Survey results indicate that the intensity of the local lighting in shoes-making industry “X” is 480 lux and 445 lux. The purpose of this study was to analyze the local illumination intensity factor against eye fatigue on workers. This research is explanatory research with cross sectional approach, the total sample is 8 people. Data analysis was performed to determine the relationship of the intensity of illumination, age, diabetes mellitus, hypertension against eye fatigue, using the chi square test. The results showed have significant relationship (p <0.05) with eye fatigue, the illumination intensity ≥ 200 (p = 0.018), workers who have aged ≥ 45 (p = 0.018), workers who have hypertension (p = 0.018) , workers who have diabetes mellitus (p = 0.710). It can be concluded that as many as 62.5% were experiencing severe eyestrain